1991
DOI: 10.1111/j.1365-2125.1991.tb03926.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose‐ranging study of UK‐68,798, a novel class III anti‐arrhythmic agent, in normal volunteers.

Abstract: (245 1) were found to be independent of dose with low levels of intra-and inter-patient variability. 4 UK-68,798 has electrophysiological effects indicative of selective class III antiarrhythmic activity and merits further assessment in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…T o date, information on the pharmacokinetics of dofetilide is limited to that obtained in man after intravenous administration (Sedgewick et al 1991, Gemmill et al 1991. In these studies the compound exhibited linear kinetics with mean plasma clearances of 4.7 and 5.2 ml/min per kg and mean terminal half-lives of 9.7 and 8.1 h. This paper reports the pharmacokinetics and metabolism in animals and man.…”
Section: Introductionmentioning
confidence: 99%
“…T o date, information on the pharmacokinetics of dofetilide is limited to that obtained in man after intravenous administration (Sedgewick et al 1991, Gemmill et al 1991. In these studies the compound exhibited linear kinetics with mean plasma clearances of 4.7 and 5.2 ml/min per kg and mean terminal half-lives of 9.7 and 8.1 h. This paper reports the pharmacokinetics and metabolism in animals and man.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was, therefore, designed to answer the question of whether dofetilide, at a clinically relevant concentration [14,15], lengthens the actionpotential duration in the hyperkalemic zone as it does in the normokalemic zone in myocardium at various pacing frequencies. The electrophysiological effects of dofetilide were examined when both [K ÷ ]o and pacing cycle length were altered in isolated guinea-pig ventricular papillary muscle.…”
mentioning
confidence: 99%
“…57,58 In clinical trials, dofetilide produced a dose-dependent effect on myocardial repolarization, as shown by a significant prolongation of the QTc interval duration on ECG. 59,60 Dofetilide does not alter the PR or QRS intervals, a finding that supports its lack of effect on conduction velocity. 61 With long-term dosing, the maximum prolongation of the QTc interval usually occurs 48 hours after start of therapy, indicating that proarrhythmic adverse effects are most likely to occur within this period.…”
Section: Dofetilidementioning
confidence: 78%
“…76 Peak plasma concentrations are typically reached within 3 hours after administration. 59,61 Plasma protein binding is estimated at 60-70%, with a volume of distribution approximately 3 L/kg. 59 Dofetilide follows a linear first-order kinetics model.…”
Section: Dofetilidementioning
confidence: 99%